Imprint cytology of osteosarcoma of the jaw: A case report - Cabral, Luiz Antonio Guimares [UNESP]; Werkman, Cristina [UNESP]; Brando, Adriana Aigotti Haberbeck [UNESP]; Almeida, Janete Dias [UNESP] (Springer Nature, 2009)
Introduction. Osteosarcomas are highly malignant bone-forming neoplasms that account for about 20% of all sarcomas. In light of their aggressive behavior, early diagnosis is crucial for determining adequate treatment. Dental professionals may be the first to detect jaw osteosarcomas in their initial stages. The aim of this case report is to draw attention to the possibility of diagnosing this tumor based on clinical, radiographical and cytological characteristics before confirmation by histology. Case presentation. A 24-year-old Afro-Brazilian man presented with swelling and pain on the left side of the mandible in the region of the third molar (tooth 38). Radiography showed a poorly delimited intraosseous lesion with radiolucent and radiopaque areas. The cytological aspects were consistent with the diagnosis of osteosarcoma, which was confirmed by biopsy. Conclusion. Imprint cytology was found to be a reliable, rapid and easy complementary examination. An early diagnosis of osteosarcoma of the jaw is fundamental to the early determination of an adequate treatment. © 2009 Cabral et al; licensee BioMed Central Ltd.
Keywords: adult; case report; cytology; histopathology; human; human tissue; jaw tumor; male; mandible resection; molar tooth; osteosarcoma; panoramic radiography; priority journal; tumor biopsy